1989
DOI: 10.1111/j.1574-6968.1989.tb02438.x
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane proteins as major antigens of Fusobacterium nucleatum

Abstract: The immunochemical reactions of rabbit polyclonal antibodies directed to different preparations of Fusobacterium nucleatum i.e, whole cells, peptidoglycan associated proteins, a peptidoglycan‐protein complex and a purified 40 kiloDalton (kDa) protein, were investigated on outer membrane preparations of Fusobacterium species and a restricted number of Leptotrichia buccalis after their separation on sodium dodecyl sulphate polyacrylamide gels and electrotransfer to nitrocellulose. All F. nucleatum strains had id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…3). Previous findings demonstrated that outer membrane proteins of F. nucleatum with molecular weights at 70, 60, 55 and 40 kDa are major immunogens [31,32]. Identification of these immunogens by proteomic approaches may be critical for development of subunit vaccines against F. nucleatum .…”
Section: Discussionmentioning
confidence: 99%
“…3). Previous findings demonstrated that outer membrane proteins of F. nucleatum with molecular weights at 70, 60, 55 and 40 kDa are major immunogens [31,32]. Identification of these immunogens by proteomic approaches may be critical for development of subunit vaccines against F. nucleatum .…”
Section: Discussionmentioning
confidence: 99%
“…For production of polyclonal sera against the Fn type strain ATCC 25586, an outer membrane protein (OMP) preparation was made from late log phase grown bacterial cells using the method of Bakken et al 10 This OMP preparation was quantified using BCA (Sigma Aldrich) and 100 lg of total protein was mixed 1:1 with Freund's incomplete adjuvant (Sigma Aldrich) and injected intraperitoneally (i.p.) into a male New Zealand white rabbit, boosting twice, each with 50 lg of OMP, 3 weeks apart.…”
Section: Production Of Anti-fn Polyclonal Seramentioning
confidence: 99%
“…It is also known that FomA is a voltage-dependent general diffusion porin [14, 15] and a virulence factor which facilitates bacterial evasion of host immune surveillance by binding the Fc fragment of human immunoglobulin G (IgG) [15]. Additionally, FomA has been recognized as a major immunogen of F. nucleatum [16, 17]. Intriguingly, it has been reported that FomA is involved in binding between fusobacteria and Streptococcus sanguis on the tooth-surface and to Porphyromonas gingivalis ( P. gingivalis ) in the periodontal pockets [18], supporting the view that FomA acts as a receptor protein in co-aggregation with other oral pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%